Protease Supplementation and its Effect on Performance and Nutrient Utilization in Broiler Chicken Fed Low Protein Diets - Salman, Chisty Syed; Nayak, Sunil; Baghel, R.P.S.; Malapure, C. D.; Govil, Kumar; Thakur, Dinesh (Indian Journal of Animal Nutrition, 2017)
The present experiment was designed to evaluate the effects of protease supplementation on performance, nutrient utilization, carcass traits and economics of broilers production. A total of 216, day old chicks were randomly assigned to nine dietary treatments and each treatment consisted of three replicates of eight chicks each. The basal diet (T1) was formulated as per ICAR (1998) specifications and contained 22% CP and 2800 kcal ME/kg diet. In treatment T2, CP content was reduced to 20%. In treatments T3, T4 and T5 the diets were same as in treatment T2 but supplemented with proteases (each g contained 600000 IU) @ 100, 200 and 300 g/tonne of feed, respectively. In treatment T6, the diet was same as in treatment T1 except CP content which was further reduced to 18%. In treatments T7, T8 and T9, the diets were same as in T6 but supplemented with protease @ 100, 200 and 300 g/tonne, respectively. The experiment was conducted for 5 weeks. The broilers fed with standard basal diet (22% CP) had a better (P<0.05) feed efficiency ratio than those fed with lower protein diets (20 and 18% CP). Supplementation of protease @ 300 g/tonne of feed to low protein diet improved (P<0.05) performance of broilers and retention of nutrients (DM, CP, CF and NFE). Different levels of protein and supplementation of protease in diets did not show any significant effect on carcass traits. Net return was improved (P<0.05) in groups fed low protein diets supplemented with protease @ 300 g/tonne as compared to unsupplemented one. Thus, it was concluded that reduction of protein from 22 to 20 and 18% reduced the performance of broilers, however, supplementation of protease @ 300 g/tonne feed in low protein diets improved their performance, retention of nutrients and economic returns.